The town chronicle of Johannes Hass: history writing and divine intervention in the early sixteenth century - Christ, M (Oxford University Press, 2016)
The council annals of Johannes Hass, the last Catholic mayor of the West Bohemian town of Görlitz, are a fascinating document. In a single source we can see the author’s changing interpretation of divine intervention between c.1509 and 1542. After the introduction of the Reformation, Hass steadily decreased the importance of God, whilst the Devil became increasingly important. Regardless of Hass’s staunch Catholicism, Martin Luther’s impact can be felt in his vision of the divine and the demonic as he subconsciously incorporated minor elements of Lutheranism and commented positively on small changes brought about by the Reformation. Hass shows how receptive Catholics were towards Lutheran theology, without necessarily acknowledging it, as long as the new religion did not challenge the urban order. In rich and colourful language, Hass changed the very nature of God, the Devil and the saints. In this way he was responding to the slow but steady introduction of the Reformation in Görlitz. Only by gradually turning God into a passive observer and giving greater agency to human actors could Hass make sense of the absence of a clear sign in favour of the Catholics in Görlitz.